International migration and schooling in the Eastern Caribbean - Simmons, Alan B.5Plaza, Dwaine E. (1992)
This paper examines the relationship between schooling and migration for the population of the Eastern Caribbean. It attempts to shed light on the two-sided role of education in these micro states--small autonomous nations with unique challenges of development associated with their size and limited natural resources. On the one hand, schooling is a vital ingredient for future development, while on the other hand, it facilitates emigration, particularly for individuals who have completed more advanced study
Keywords: Migration